THE IMPLEMENTATION OF WHATSAPP AND ZOOM APPLICATION IN PUBLIC SPEAKING COURSE DURING COVID-19 PANDEMIC AT IAIN PALANGKA RAYA - Mukaromah Mukaromah; Imam Qalyubi; Rahmadi Nirwanto (PROJECT (Professional Journal of English Education), 2022)
This research aimed to describe the implementation of Whatsapp and Zoom application, the strength and the weaknesses of Whatsapp and Zoom in online learning. This research was carried out at IAIN Palangka Raya. This study was used a qualitative approach. The data was taken through interview and documentation. The participants of this research were eight students from IAIN Palangka Raya. The sample were taken based on the purposive sampling technique. The result of the study are : Whatsapp and Zoom are two applications that can help students to practice English, make learning process more effective, and facilitate the lecturer-students interaction and communication. It provides many features to support the learning process for sharing information and can give positive contribution to help in online learning. The dominant problems to apply them are bad internet connection, need a lot of money to buy quota and lack of supporting facility for internet. Keywords:  Implementation, Whatsapp, Zoom, Public Speaking Course, Covid-19 Pandemic